From Mosque to Smartphone: The Digital Transformation of Islamic Da’wah and Counseling - Putri, Fillaila Novia; Wildana, Syarifah Auliya; Alfiani, Yuldiya Husniya (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study explores the transformation of Islamic da’wah and counseling from traditional mosque-based practices to digital platforms in the era of technological advancement. Historically, mosques have served not only as centers of worship but also as hubs of education, moral guidance, and social development within Muslim communities. The traditional roles of scholars, kiai, and local preachers as authentic sources of Islamic knowledge have been gradually complemented and, in some cases, redefined by digital preachers, influencers, and online educators. The rise of the “virtual mosque” phenomenon, supported by platforms such as YouTube, Instagram, TikTok, and podcasts, has expanded the reach of Islamic teachings, offering flexible, accessible, and creative forms of communication that transcend geographical boundaries. Using a qualitative library research approach, this paper analyzes 35 scholarly articles that discuss the evolution of da’wah and Islamic counseling in the digital era. The findings reveal significant transformations in three main aspects: the preacher’s role, audience engagement, and the adaptation of religious content. Digital counseling, meanwhile, emerges as an alternative form of spiritual and psychological support that integrates Islamic values into modern communication systems. Despite offering wide accessibility, cost efficiency, and interactivity, digital da’wah and counseling also face challenges such as misinformation, lack of emotional depth, ethical dilemmas, algorithmic bias, and the risk of misinterpreting Islamic teachings. This study concludes that the digital transformation of da’wah and Islamic counseling requires a balanced approach that preserves the authenticity, ethics, and spiritual essence of traditional Islamic teachings while embracing the opportunities of digital innovation to reach contemporary audiences more effectively.